Implementasi Model Problem Based Learning (PBL) Dalam Menumbuhkan Semangat Belajar Siswa Kelas X Pada Pembelajaran Akidah Akhlak Di MA Takhassus Al-Qur’an 1 Mojotengah - Mala Nafisah; Ali Mu’tafi; Hidayat Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Student motivation is one of the key factors in successful learning, particularly in the subject of Akidah Akhlak. This study aims to examine the implementation of the Problem-Based Learning (PBL) model in fostering student motivation in Grade X, its impact on student enthusiasm and engagement in learning, as well as the factors that support and hinder its implementation at MA Takhassus Al-Qur’an 1 Mojotengah. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the PBL model is systematically implemented through five main stages and is able to enhance active participation, critical thinking, independence, and intrinsic motivation among students. The success of PBL implementation is supported by high student involvement, teacher support, and a supportive learning environment. However, challenges such as uneven participation within groups, time constraints, and teachers' readiness in designing learning scenarios still require attention. Overall, the PBL model has proven effective in fostering students' learning enthusiasm and is worthy of further development in Akidah Akhlak education.